The Correlation Between the Nutritional Condition of Undergraduate Students at Mulawarman University and the Frequency of Fast Food Consumption and Balanced Nutritional Knowledge Level - Sabrina, Annida; Khotimah, Siti; Rahayu, Hanis Kusumawati (Fakultas Kedokteran, 2024)
Background: Nutritional status is an important factor because it relates to intelligence, productivity and creativity so that it can affect the quality of human resources. Research related to nutritional status aimed to determine the relationship between the frequency of eating fast food and nutritional status, and to determine the relationship between the level of knowledge of balanced nutrition and nutritional status. Methods: The research design used an analytic observational research method with a cross sectional observational approach. Statistical analysis was performed using the Chi-Square Test. The study population was students of the undergraduate study program at Medical Faculty, Mulawarman University who were willing and had met the inclusion criteria. In this study, it was found that 168 respondents met the inclusion criteria. Result: The conclusions obtained from the results of this study were: There was no relationship between the frequency of eating fast food and nutritional status with a p-value = 0.379 There was no relationship between the level of balanced nutrition knowledge and nutritional status with a p-value = 0.384. Conclusions: It can be concluded that there is no relationship between the frequency of eating fast food and the level of knowledge of balanced nutrition with nutritional status.